2019
DOI: 10.1007/s00394-019-01998-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin K with cardiovascular events and all-cause mortality: a systematic review and meta-analysis

Abstract: Association of vitamin K with cardiovascular events and all-cause mortality: a systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 64 publications
3
60
1
Order By: Relevance
“…Measuring levels of dp-ucMGP has previously been proven to be a useful method to assess vitamin K status [22]. Dp-ucMGP inversely relates to mortality and other clinical meaningful endpoints in various cohorts [12,15,[23][24][25][26][27][28][29][30]. Supplementation of vitamin K has a reducing effect on dp-ucMGP levels [22,31], and the opposite holds true with regard of the use of VKAs [22,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Measuring levels of dp-ucMGP has previously been proven to be a useful method to assess vitamin K status [22]. Dp-ucMGP inversely relates to mortality and other clinical meaningful endpoints in various cohorts [12,15,[23][24][25][26][27][28][29][30]. Supplementation of vitamin K has a reducing effect on dp-ucMGP levels [22,31], and the opposite holds true with regard of the use of VKAs [22,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two separate meta-analyses were conducted to investigate the possible association between dp-ucMGP and CV mortality and morbidity. Chen et al included 21 studies and 222,592 participants and reported that high plasma dp-ucMGP was strongly associated with increased risk for all cause and CV mortality [ 32 ]. Similarly, another meta-analysis of 11 studies and 33,289 patients showed that circulating dp-ucMGP was associated with high risk for total mortality (HR = 1.77) and CV mortality (HR = 1.84), whereas no association was found between dp-ucMGP and CV disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these results, data from the Third National Health and Nutrition Examination Survey (NHANES III) and Prevention of Renal and Vascular End-Stage Disease (PREVEND) studies showed that vitamin K deficiency was a strong, independent predictor of CVD, mortality and incidence of CKD (55,56). Chen et al, conducted a meta-analysis of 21 studies including 222,592 subjects and found that both daily dietary consumption of K1 and K2 were associated with aortic calcification (57). Several studies reported that CKD patients present with a significant -often underdiagnosed-deficiency of vitamin K, which is gradually increased along with deterioration of renal function and is more pronounced in dialysis patients.…”
Section: Vitamin K: the Essential Co-factor Of Mgpmentioning
confidence: 75%